Sosialisasi dan Pelatihan Pengolahan Limbah Plastik: Langkah Menuju Kehidupan Berkelanjutan di Kelurahan Cibodas Baru Kota Tangerang - Siti Asriah Immawati; Rosyid Rosyid; Humairoh Humairoh (Jurnal Pengabdian Masyarakat, 2024)
Plastic waste has become one of the most pressing environmental issues in the 21st century, with Indonesia as one of the largest contributors. This research aims to socialize plastic waste treatment in Cibodas Baru Urban Village, Tangerang City, with a focus on increasing community awareness and participation, particularly housewives, in the recycling process. The methods used included an initial survey, socialization sessions, and practical training in making reusable shopping bags from plastic waste. The results showed a significant increase in participants' understanding of waste management and their ability to process plastic into functional products. This initiative not only reduces plastic waste, but also empowers women economically by providing skills that can generate income. Moreover, it also contributes to sustainable development goals by promoting environmentally friendly practices. This study emphasizes the importance of community engagement and collaborative efforts in addressing plastic waste issues, paving the way towards a cleaner and more sustainable environment.